Recent advances in microwave-absorbing materials fabricated using organic conductive polymers - Peymanfar, Reza; Dogari, Haniyeh; Selseleh-Zakerin, Elnaz; Hedayatzadeh, Mohammad Hossein; Daneshvar, Sara; Amiri-Ramsheh, Nasim; Ghafuri, Hossein; Mirkhan, Ali; Ji, Guangbin; Aslibeiki, Bagher (Frontiers in Materials, 2023)
Microwave absorbing materials are widely utilized in military and civilian applications. Moreover, their environmental potential to refine electromagnetic pollution has promoted their importance. An ideal conjugated organic polymer as a microwave absorbing material should possess a high porosity, low density, long conjugated backbone, narrow energy band gap, proper conductive and relaxation loss, as well as vast specific surface area. The presented review is gathering the conductive polymer types used as microwave absorbing material and their composites toward improving the microwave absorbing capability. Additionally, the recent developments in synthetic strategies and structural properties of pure carbon-based microwave absorbing materials and other conjugated structures having heteroatoms in their chains are discussed. In the field of microwave absorbers, the common microwave absorbing mechanisms commanding in the conductive polymers and their composites as well as the special mechanisms tuning microwave absorbing characteristics including metamaterial and quasi-antenna features were scrupulously dissected. The presented review sheds new light on architecting low-density and high-performance microwave absorbing structures and offers new prospects in tailoring conjugated polymers based on their dominant mechanisms.